Numerical analysis of cam and follower based on the interactive design approach - Al-Hamood, Amjad; Jamali, Hazim U.; Abdullah, Oday I.; Senatore, Adolfo; Kaleli, Hakan (SPRINGER HEIDELBERG, 2019)
The contact between the cam and follower is considered as one of the most complicated problems from the lubrication point of view. The contact in this elastohydrodynamic lubrication (EHL) problem undergoes extreme variation conditions of different parameters. These include the load variation, geometry at the contact point and sliding speed. This paper presents an EHL solution for the contact problem between cam and chamfered follower (originally flat faced). The model of solution is point contact in order to accurately simulate the chamfering of the follower. The solution of Reynolds equation considers the non- Newtonian oil behavior in the calculation of the flow factors. The interactive design approach used in this paper focused mainly on the effect of chamfer as well as the other general parameters of the mechanism. The results revealed that chamfering of the follower in the axial direction has considerable effects on the performance of the mechanism. The linear modification causes significant rise in the maximum pressure and extreme thinning in the film thickness.
Keywords: Cam; Follower modification; Non-Newtonian; Elastohydrodynamic lubrication; LUBRICATION; BEHAVIOR; Engineering